Tourist Loyalty Model Visiting Culinary Tourism Destinations - Heri Setiawan; Abd Hamid; Jusmawi Bustan; Ummasyroh (Universitas Pendidikan Ganesha, 2023)
Most of the culinary tourism destinations in Palembang City have not opened to serve visitors since the Covid-19 pandemic occurred in early 2020. This has an impact on the intensity of tourist visits to culinary tourism destinations in Palembang City which has decreased. Then, decrease in the culinary experience, cleanliness, comfort of culinary tourism destinations, and destination management services. The purpose of the study was to analyze the connection between the experience of tourists, value perception, destination quality, satisfaction, and tourist loyalty. The type of research is quantitative research with a causality approach. The population of the study is local travelers who have come to culinary tourism destinations in Palembang at least 2 times. Purposive sampling was used to determine the respondents with a sample of 216. Structural equations are used as a method of analysis. The outcomes of the study explain that there is no linear association betwixt tourist experience and satisfaction of tourists. Value of perception, destination quality, and satisfaction of tourists are linearly related. Tourist experience, destination quality, and tourist loyalty are not linearly related. Value perception and tourist loyalty are linearly related. Then, tourist satisfaction and tourist loyalty are linearly related. This research can be a reference for tourist destination managers to maintain the loyalty of tourists visiting culinary tourism destinations, and become a reference for the next research in destination marketing.